Synthesis of NR-g-PMMA by "grafting from" method using ATRP process - Lapporn Vayachuta (2018)
Grafting poly(methyl methacrylate) or PMMA from natural rubber (NR) using ATRP process, NR has to be transformed into bromoalkyl-functionalized NR (NRBr) acting as ATRP macroinitiator. The NRBr was prepared by two-step chemical modification i.e., epoxidation and epoxide ring opening reaction using a nucleophile containing bromine atom such as 2-bromopropionic acid (A1) and 2-bromo-2-methylpropionic acid (A2). The fixation of A1 and A2 on 4-methyl-4-octene, a model representing one repeat unit of NR, modified by epoxidation was prior studied and it was found that the resulting addition products from A2 using as ATRP initiator for MMA gave a better control of M n,exp and low PDI of PMMA than that from A1. Then, the NR was transformed into ATRP rubber macroinitiator via epoxidation, followed by epoxide ring addition with only A2. 1 H NMR was employed to determine the amount of A2 addition units on NR, which is considered to be the same amount of grafting sites for ATRP of MMA. The grafting of PMMA was then successfully carried out from the NR backbone by ATRP process. The PMMA grafts of the NR-g-PMMA were indeed linked to the NR backbone via ester linkage of the A2 unit. The PMMA grafts could be cleaved from the NR backbone by acid hydrolysis, while PMMA grafting by other conventional radical reaction could not be done. Then, the average MW of PMMA grafts after separation using acetone extraction was evaluated. © 2011 Wiley Periodicals, Inc.